Birthright : people and nature in the modern world - Kellert, Stephen R. (Yale University Press, 2012)
Human health and wellbeing is inextricably linked to nature; our connection to the natural world is part of our biological inheritance. In this book, a pioneer in the field of biophilia, the study of human beings' inherent affinity for nature, sets forth the first full account of nature's powerful influence on the quality of our lives.